Literature Review on Children Outside Educational Opportunities: A Study of Children with Foreign Origin in Japan - Ohsaka, Yuki (Indonesian Social Work Consortium (ISWC), 2024)
Children of foreign origin in Japan face various hurdles in accessing educational opportunities, potentially limiting their strengths and abilities throughout their life course. With the aim of increasing the inclusion of children of foreign origin in Japanese formal education, this paper reviews the literature, focusing on early childhood education and care (ECEC) to identify what has been clarified in previous studies and what has not been sufficiently analyzed, to suggest future directions. Compared with the extensive studies conducted in the U.S., research on ECEC opportunities for children of foreign origin living in Japan is still in its nascent stage. To ensure access to ECEC for children of foreign origin in Japan, it is critical to examine the impact of ECEC on children of foreign origin in Japan and determine which types of ECEC are most effective. Also, there is a lack of comprehensive research on the specific nationalities, family environments, living conditions, cultural backgrounds, and attitudes of parents who do not utilize ECEC opportunities, and detailed research involving parents of children not enrolled in ECEC is necessary to understand the barriers and decision-making factors related to ECEC enrollment.